(3bdejI LdGd GdOjf GdOhGfis - (3LdGd GdOjf eMeO Hf CSYO GdUOjbj GdOhGfj, GdOhGfj,J (B918 (3g` s ((3eMeO Hf Rjf GdOjf gdGd s)
(3ChdgG (B:s
(3f(B" (3hGdbde heG jSWQhf gPg PcQg dbhe jYbdhf aGSJeY deG jJdi Ydjc s
(3BNQgG (B:s
(3Ydi UaMGJ GdCOhGQ JQhi HMb ef fSN GdcJH GdSGdaI Gdbde hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3JUhas
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B32s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B266) s
Keywords: (3GdeLGejYs